An Gambaran Umum Perilaku Tenaga Kesehatan Yang Meningkatkan Angka Penularan COVID-19 - Sylviasari Risgiantini (Yayasan Pendidikan Medika Indonesia, 2023)
This study aims to determine the behavior of health workers while providing care to COVID-19 patients which causes an increase in transmission among health workers. The research was conducted using the Literature Review method by taking data from journals that raised cases of COVID-19 transmission among health workers. From the search conducted, it was found that the behavior of health workers who had the opportunity to increase the transmission rate was behavior that was more likely to be a daily habit that was carried out unconsciously, that are touching the cheeks, nose or mouth with their hands after interacting with patients. Another behavior is the lack of awareness to always wear masks and Personal Protective Equipment (PPE), decreased concentration due to fatigue caused by long working hours, high workload and limited resources during works. The difference of the level of knowledge in theory and practice in the field is also one of the causes for these behaviors to occur. kers. From the search conducted, it was found that the behavior of health workers who had the opportunity to increase the transmission rate was behavior that was more likely to be a daily habit that was carried out unconsciously, namely touching the cheeks, nose or mouth with their hands after interacting with patients. Another behavior is the lack of awareness to always wear masks and Personal Protective Equipment (PPE), due to decreased concentration due to fatigue due to long working hours, high workload and limited resources while carrying out tasks. The difference in the level of knowledge in theory and practice that occurs in the field is also one of the causes for these behaviors to occur.